Family structure of F5 soybeans lines derived from soybean varieties with the main differences on seed size and maturity traits - Heru Kuswantoro; RINA ARTARI; RUDI ISWANTO; HILYATUL IMANI (Society for Indonesian Biodiversity, 2020)
Abstract. Kuswantoro H, Artari R, Iswanto R, Imani H. 2020. Family structure of F5 soybeans lines derived from soybean varieties with the main differences in seed size and maturity traits. Biodiversitas 21: 2576-2585. The success of breeding programs depends on the availability of genetic resources with high genetic diversity. Genetic diversity plays a role in relationship between genotypes or within a group of genotypes. Seed size and the days to maturity are the main traits to develop a new superior variety for better seed quality and quantity. The plant materials consisted of eight F5 families originating from a combination of crossbreeding between four Korean soybean varieties (Daehwang, Daemang, Daewon, and Songhak) and two Indonesian soybean varieties (Argomulyo and Lawit). The main traits of four Korean soybean varieties are similar to each other, i.e. large seed size and early maturity. The two Indonesian soybean varieties differ on seed size and maturity. Argomulyo has a large seed size and early maturity, while Lawit has a small seed size and late maturity. Agronomic data, such as days to 50% flowering, days to maturity, days to harvesting, plant height, number of branches, number of reproductive nodes, number of filled pods, number of unfilled pods, seed yield per plant, 100 seeds weight, and seed yield per plot, were analyzed using R programs to form the groups. The grouping was based on principal component analysis. The results showed that the family structure of a cross was determined by the characteristics of the crossed genotypes. The family structures with Argomulyo as male parents were more influenced by 100 seeds weight, while the family structures with Lawit as male parents were more influenced by days to maturity. No family structure was formed with a large seed size on crossing with Lawit as the male parent. In this population, high seed yield as the main target of plant breeding was obtained on crossing of Daemang with Lawit.